TESTIMONY OF SENATOR FRANK R. LAUTENBERG H. R. 969 / S. 1524 -- THE AIRLINE CABIN AIR QUALITY ACT OF 1995 (19950000) HOUSE AVIATION SUBCOMMITTEE. SUBCOMMITTEE ON TRANSPORTATION AND INFRASTRUCTURE JULY 16, 1996 (19960716). - LAUTENBERG, FRANK (Tufts Archival Research Center, 2007)
Marginalia; Testimony of Senator Frank Lautenberg supporting legislation banning smoking on international flights to and from the United States. Discusses health effects of environmental tobacco smoke on passengers and flight crew members, as well as discomfort and irritation. Particularly addresses issue of flight attendants and their health problems tied to passive smoke. Provides examples from other countries and airlines already implementing smoking bans.